POLA PENDIDIKAN AKHLAK PADA ANAK PRAREMAJA DI LINGKUNGAN KELUARGA (STUDI KASUS DI KEL. TALANG SALING KEC. SELUMA KAB. SELUMA PROPINSI BENGKULU) - Budi Erliyanto (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Gutter Saling is a village located  in Seluma is located  in the District Seluma District, which has made  the expansion in2003, which split from  South  Bengkulu, the  result  of the  division, is certainly  going to change the  order of life, whether from the government, in terms of revenue, culture, infrastructure, people’s  behavior, both  in terms of children ages pre-teens, teens, adults, or even parents themselves,  so that with the changes  become Seluma,  people in the Village of Salado Saling into society began  gradually  leave traditional traditions that  have been  there, so do not  have a traditional or a new life style, resulting in behavior  or morals are not good in everyday life, which ultimately  lead to non  selarasan  in behavior.  This study used a qualitative descriptive  approach. In obtaining the data, the authors using observation, interviews, and documentation of previous research. From the  research inidi get the  result  that  moral  education is adopted by parents in the  family in child  preteen in the  Village of Talang  Saling District of Seluma not been  implemented properly by parents who have children with pre-teens, because  there are many parents who do not implement it, most parents just rebuked him away without  giving punishment to his son. As well as the pattern of moral  education of children of pre teen  in the family environment Village of Talang  Saling District of Seluma applied by parents is lacking once  adopted by parents in the  family environment, these  are all visible from  the  percentage of parents just give the pattern direction, that each what we do have consequences, should  the parents were able to give firmness to provide  education to their  children so that  the  pattern can be complied with and  implemented in everyday life